Comorbid social anxiety disorder in patients with alcohol use disorder: A systematic review. (November 2018) - Oliveira, Lucas Mendes; Bermudez, Mariane Bagatin; Macedo, Malu Joyce de Amorim; Passos, Ives Cavalcante
Abstract: Introduction: Lifetime prevalence of social anxiety disorder (SAD) among patients with alcohol dependence is around 11%. However, no systematic review has assessed the effect of comorbid SAD on the clinical outcomes of patients with alcohol use disorder (AUD). Objectives: We aimed to compare clinical outcomes, such as alcohol relapse, suicide attempts, treatment response, readmissions, psychiatric comorbidities, and treatment compliance between patients with AUD and comorbid SAD versus patients with AUD without SAD. Methods: We carried out a systematic review by searching PubMed for articles published between January 1, 1960 and May 6, 2018. Inclusion criteria were met if a study reported a dichotomous sample of adult patients with AUD and SAD compared to patients with AUD without SAD. Review articles and preclinical studies were excluded. From the eligible studies, we extracted outcomes of interest, such as alcohol relapse, suicidal thoughts, suicide plan and attempts, treatment response, readmissions, psychiatric comorbidities, and treatment compliance. Results: Patients with both AUD and SAD have a higher prevalence of psychiatric comorbidities, mainly major depressive disorder (MDD), and depressive symptoms. In addition, they have poor treatment compliance. Conversely, the impact of comorbid SAD on alcohol relapse is controversial and current studies have yielded mixed results. Only one study assessed the impact of comorbid SAD on treatment response and showed no association. Furthermore, one study assessed suicidality and found higher rates of suicidal thoughts, suicide plans and attempts in patients with AUD and SAD. Conclusion: The present systematic review shows that it is important to screen for other psychiatric comorbidities (especially MDD), suicidality, and improve treatment adherence in patients with AUD and comorbid SAD. Future prospective studies should clarify the impact of comorbid SAD.